Effect of Winglets on Improving Wind Turbine Performance - Handayani, Sri Utami (Vocational College of Universitas Diponegoro, 2021)
Indonesia, with the longest coastline in the world, has enormous potential to develop large-scale wind energy. In wind turbines, the formation of a wake behind the wind turbine can reduce efficiency. It is estimated that the formation of a vortex tip behind the wind turbine blade can be reduced by adding a winglet. The main function of winglets attached to the blade is to reduce the effect of the wingtip vortices which are generated due to 3D spanwise flow that occurs because of the pressure non- equalization between the upper and lower blade surfaces. This paper aims to summarize the results of research on the effect of adding winglets to wind turbines.